Xanthogranulomatous pyelonephritis presenting as a pseudotumour - Chlif, Mohamed; Chakroun, Marouene; Ben Rhouma, Sami; Ben Chehida, Mohamed Ali; Sellami, Ahmed; Gargouri, Mohamed Mourad; Nouira, Yassine (Canadian Urological Association Journal, 2016)
Introduction: Xanthogranulomatous pyelonephritis (XGPN) is an atypical form of chronic pyelonephritis referred to as the ‘‘great imitator’’ because the clinical and radiological findings closely resemble other pathological entities, especially for the focal forms. Distinguishing focal XGPN from renal cancer is preoperatively difficult. Methods: We report a total number of 12 pseudotumoural XGPN cases diagnosed and treated in our department. The aim of this study is to try to better understand the clinicopathological profile of XGPN and improve its management. Results: The mean age of patients was 51.52 years. Gender ratio was 0.71. An obstructive renal calculus was noticed in nine patients (75%). Only one patient (8.3 %) presented with loin pain associated with fever, weight loss, asthenia, and increased biological inflammation markers. A bifocal mass was noticed in one case (8.3 %). The average size of the tumour was 6.58 cm. The mass was cystic in three cases (25 %). Perinephral fat strand, thickening of Gerota’s fascia, hydronephrosis, and presence of renal calculi was noticed in all solid tumour cases. XGPN was suspected in only one case (8.3%), a percutaneous biopsy showed XGPN lesions treated by antibiotics and a double J drainage. Radical nephrectomy was performed in eight patients (66.7 %) and three patients underwent partial nephrectomy (25 %). No recurrence of XGPN has been noted. Conclusion: Pseudotumoural XGPN is a rare benign disease of the kidney. Its treatment should be conservative. Lack of knowledge of this disease may explain the high rate of abusive nephrectomies. These data should be considered in the future.